Ferroic multipolar order and disorder in cyanoelpasolite molecular perovskites - Coates, CS; Gray, HJ; Bulled, JM; Boström, HLB; Simonov, A; Goodwin, AL (Royal Society, 2019)
We use a combination of variable-temperature high-resolution synchrotron X-ray powder diffraction measurements and Monte Carlo simulations to characterize the evolution of two different types of ferroic multipolar order in a series of cyanoelpasolite molecular perovskites. We show that ferroquadrupolar order in [C3N2H5]2Rb[Co(CN)6] is a first-order process that is well described by a four-state Potts model on the simple cubic lattice. Likewise, ferrooctupolar order in [NMe4]2B[Co(CN)6] (B = K, Rb, Cs) also emerges via a first-order transition that now corresponds to a six-state Potts model. Hence, for these particular cases, the dominant symmetry breaking mechanisms are well understood in terms of simple statistical mechanical models. By varying composition, we find that the effective coupling between multipolar degrees of freedom-and hence the temperature at which ferromultipolar order emerges-can be tuned in a chemically sensible manner. This article is part of the theme issue 'Mineralomimesis: natural and synthetic frameworks in science and technology'.